The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.52547/wjps.10.2.33
|View full text |Cite
|
Sign up to set email alerts
|

The Gracilis Muscle Flap: A “Work Horse” Free Flap in Diabetic Foot Reconstruction

Abstract: BACKGROUNDDiabetes is a leading cause of foot ulcers and lower limb amputation throughout the world. Adequate wound debridement and cover is the standard of care, but lack of adequate vascularised local tissue poses a major challenge. The gracilis flap offers various advantages in this respect, which we would like to discuss in this study, and hence makes it an attractive option in diabetic foot patients. MATERIAL AND METHODSThis retrospective study was conducted over a period of 2 years, from 2018 to 2020 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Although chimeric flaps can be used to reconstruct DFUs with dead cavities, 41 the repaired skin grafts often become bulky and require secondary surgery for debulking, with the risk of damaging the cutaneous nerves during flap harvesting. Free muscle flaps have advantages such as shorter operation time, sufficient size, ability to fill dead cavities, abundant blood supply, strong anti‐infection capabilities, good contour appearance and no damage to cutaneous nerves 17,42,43 . Therefore, combining free muscle flaps with STSGs may be an ideal choice for DFU reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although chimeric flaps can be used to reconstruct DFUs with dead cavities, 41 the repaired skin grafts often become bulky and require secondary surgery for debulking, with the risk of damaging the cutaneous nerves during flap harvesting. Free muscle flaps have advantages such as shorter operation time, sufficient size, ability to fill dead cavities, abundant blood supply, strong anti‐infection capabilities, good contour appearance and no damage to cutaneous nerves 17,42,43 . Therefore, combining free muscle flaps with STSGs may be an ideal choice for DFU reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Free muscle flaps have advantages such as shorter operation time, sufficient size, ability to fill dead cavities, abundant blood supply, strong anti‐infection capabilities, good contour appearance and no damage to cutaneous nerves. 17 , 42 , 43 Therefore, combining free muscle flaps with STSGs may be an ideal choice for DFU reconstruction. Mayr‐Riedler et al 44 found that the risk of significant complications in reconstructing the forefoot using free fasciocutaneous flaps is four times higher than that of free muscle flaps, especially in elderly patients with ischaemic defects.…”
Section: Discussionmentioning
confidence: 99%
“…This flap is versatile due to the amount of soft tissue available and the consistent vascular supply (Urken, 2012). It is widely used for postoncological breast reconstruction and advanced diabetic foot complications without significant donor site and functional morbidities (Shyamsundar et al, 2021; Siegwart et al, 2021). In head and neck surgery, it was proposed as a valuable alternative in salvage laryngectomies (Jing et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some interesting findings have been reported by Simsek et al (2017), who used this flap to manage extended orbital exenterations. We preferred the gracilis muscle free flap because of the minimal donor site morbidity and the optimal functional outcome that this option has widely demonstrated in the current literature (Shyamsundar et al, 2021; Siegwart et al, 2021).…”
Section: Discussionmentioning
confidence: 99%